Two Cases of Neisseria meningitidis Proctitis in HIV-Positive Men Who Have Sex with Men - Gutierrez-Fernandez, José (Emerg Infect Dis, 2017)
We report 2 cases from Spain of infectious proctitis caused by Neisseria meningitidis in HIV-positive men who have sex with men. Genetic characterization of the isolates showed that they are unusual strains not found in other more frequent meningococcal locations. This finding suggests an association between specific strains and anogenital tract colonization.